Do therapeutic imagery practices affect physiological and emotional indicators of threat in high self‐critics?. (28th October 2014) - Duarte, Joana; McEwan, Kirsten; Barnes, Christopher; Gilbert, Paul; Maratos, Frances A.
<x xml:space="preserve">Abstract</x> Objectives Imagery is known to be a powerful means of stimulating various physiological processes and is increasingly used within standard psychological therapies. Compassion‐focused imagery (CFI) has been used to stimulate affiliative emotion in people with mental health problems. However, evidence suggests that self‐critical individuals may have particular difficulties in this domain with single trials. The aim of the present study was to further investigate the role of self‐criticism in responsiveness to CFI by specifically pre‐selecting participants based on trait self‐criticism. Design Using the Forms of Self‐Criticism/Self‐Reassuring Scale, 29 individuals from a total sample of 139 were pre‐selected to determine how self‐criticism impacts upon an initial instance of imagery. Methods All participants took part in three activities: a control imagery intervention (useable data N = 25), a standard CFI intervention (useable data N = 25), and a non‐intervention control (useable data N = 24). Physiological measurements (alpha amylase) as well as questionnaire measures of emotional responding (i.e., the Positive and Negative Affect Schedule, the Types of Positive Affect Scale, and the State Adult Attachment Scale) were taken before and after the different interventions. Results Following both imagery interventions, repeated measures analyses revealed that alpha amylase increased significantly for high self‐critics compared with low self‐critics. High self‐critics (HSC) also reported greater insecurity on entering the imagery session and more negative CFI experiences compared with low self‐critics. Conclusions Data demonstrate that HSC respond negatively to imagery interventions in a single trial. This highlights that imagery focused therapies (e.g., CFI) need interventions that manage fears, blocks, and resistances to the techniques, particularly in HSC. Practitioner points An initial instance of imagery (e.g., CFI) can be frightening for people who have a tendency to be self‐critical. This research provides examples of physiological and emotional responses to imagery type therapies in high and low self‐critics, and associated clinical implications. Therapists may find it helpful to be mindful that when introducing imagery based therapies, highly self‐critical patients need interventions that manage fears, blocks, and resistances to the techniques.